The Utilization of Audio-Visual Media in IPAS Learning for Third-Grade Students at SD Negeri 07 Enam Lingkung - Serly Aprina; Stavinibelia Stavinibelia; Yona Syaida Oktira; Ayunis Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by The use of audiovisual media in science learning in third grade at SD Negeri 07 Enam Lingkung shows significant potential for increasing student interest and understanding. This study used a qualitative approach involving observations and interviews with teachers and students. The results indicate that the use of media such as video and animation not only makes learning more engaging but also encourages active student engagement. Despite challenges related to facilities and infrastructure and teachers' skills in operating the media, efforts to effectively implement audiovisual media can create a more interactive and enjoyable learning environment, thereby improving student learning outcomes. Through the use of educational videos and animations, students more easily understand complex concepts and feel more engaged in the learning process. Despite challenges related to facilities and teacher skills, the implementation of audiovisual media successfully increased student motivation and enthusiasm, creating an interactive and enjoyable learning atmosphere. The results of this study emphasize the importance of integrating audiovisual media into learning strategies to improve the quality of education in elementary schools.